Looking beyond the Horizon: How to Approach the Customers' Customers in Business-to-Business Markets. (September 2014) - Homburg, Christian; Wilczek, Halina; Hahn, Alexander
Suppliers in business-to-business (B2B) markets often approach their customers' customers with marketing activities. However, marketing research lacks an integrative conceptualization of this phenomenon. The authors address this void by conceptualizing a B2B supplier's marketing approaches to indirect customers. Drawing on a literature review and a qualitative empirical study, the authors identify three indirect customer marketing approaches: direct customer downstream support, cooperative indirect customer marketing, and independent indirect customer marketing. They also propose external (value chain–related) and internal (B2B supplier–related) moderators that influence the relationship between a B2B supplier's marketing approaches to indirect customers and its financial performance. The authors argue that although power constellations and product value contribution in the value chain determine the specific indirect customer marketing approach that will lead to financial success, internal professionalization of a B2B supplier's organizational structure and processes further strengthens the positive financial impact of each approach.